RANCANG BANGUN WEBSITE E-LIBRARY PADA TUNAS MULIA MONTESSORI SCHOOL - Adhi Kusnadi; Fenina Adline Twince Tobing; Yaman Khaeruzzaman; Dennis Gunawan; Wirawan Istiono; Alexander Waworuntu; Maria Irmina Prasetiyowati (Prioritas: Jurnal Pengabdian Kepada Masyarakat, 2023)
A website is a collection of pages that contain specific information and can be accessed by anyone, anytime easily through an internet connection. Websites have become one of the facilities of the internet that can make life easier. The various positive impacts provided by website technology offer convenience to users. One of them is an E-library to obtain the necessary information for research or simply for reading. Almost all schools have implemented this technology, and Tunas Mulia Montessori School is also eager to build an E-library. The realization of this goal is assisted by Multimedia Nusantara University, which has the technological capabilities. The website development method used is the SDLC (System Development Life Cycle) concept, which is a process used by system analysts to develop an information system. The presence of the E-Library website has greatly impressed Tunas Mulia. This can be seen from the school's enthusiasm during the presentation of the results and the survey, where all questions were answered with satisfaction and great satisfaction